2010
DOI: 10.3390/rs2040990
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Vegetation Phenological Cycles in Two Different Semi-Arid Environmental Settings Using a Ground-Based NDVI System: A Potential Approach to Improve Satellite Data Interpretation

Abstract: Abstract:In semi-arid environmental settings with sparse canopy covers, obtaining remotely sensed information on soil and vegetative growth characteristics at finer spatial and temporal scales than most satellite platforms is crucial for validating and interpreting satellite data sets. In this study, we used a ground-based NDVI system to provide continuous time series analysis of individual shrub species and soil surface characteristics in two different semi-arid environmental settings located in the Great Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
(40 reference statements)
0
28
0
Order By: Relevance
“…Vegetation in arid environments is characterized by open canopies with significant background (leaf litter, dead branches, shadows, and soil) making it difficult to isolate the green vegetation reflectance signal from the canopy background signal [34]. Mapping and estimating vegetation cover in arid areas at detailed scales is hindered by the sparsity of vegetation and the influence of soil background reflectance in the spectral data [15,17,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation in arid environments is characterized by open canopies with significant background (leaf litter, dead branches, shadows, and soil) making it difficult to isolate the green vegetation reflectance signal from the canopy background signal [34]. Mapping and estimating vegetation cover in arid areas at detailed scales is hindered by the sparsity of vegetation and the influence of soil background reflectance in the spectral data [15,17,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown strong relationships between NDVI and biophysical properties such as leaf area index (LAI) [9], fraction of photosynthetically active radiation (fPAR) [10], areal vegetation fraction [11][12][13][14], net and gross primary productivity [15], chlorophyll abundance [16], and biomass [17]. It should be pointed out that areas not covered by vegetation may still show variations in NDVI due to atmospheric variations such as water vapor and aerosols, soil conditions as well as sensor characteristics [18].…”
Section: Introductionmentioning
confidence: 99%
“…This is further supported by the in situ NDVI time series, where no straight forward relation between NDVI, either the maximum or the seasonal integral, is observed as compared to biomass e.g., the maximum NDVI values were observed on the year of lowest biomass production (2006), but the four years of data are insufficient for conclusions. Previous study using in situ data in a semi-arid environment has shown high temporal resolution NDVI to be able to distinguish between the same species exposed to different growing conditions, but for sites where the vegetation is dominated by the perennial Sarcobatus vermiculatus (greasewood) [62]. Therefore study into the extent that natural variation in species composition affects satellite based vegetation water indices and vegetation greenness indices, would provide some important perspectives for interpreting these indices for the Sahel.…”
Section: Land Surface Moisture During Period Of Vegetation Growthmentioning
confidence: 99%